Designing A Balanced Scorecard As A Performance Measuring Tool In Off-Street Parking Management Services Companies In Indonesia (Case Study Pt. Bahana Security System) - Panjaitan, Felix; Harianto, Eric (Pascasarjana STIE Amkop Makassar, 2024)
In facing an increasingly competitive business environment, a tool is needed that can be used by management to measure company performance. Balanced Scorecard (BSC) is a very appropriate method to use to measure company performance accurately and accountability. BSC itself measures company performance from several perspectives such as a financial perspective, customer perspective, learning and growth perspective. as well as an internal business process perspective. This research was conducted at PT. Bahana Security System from January 2022 to June 2023. This research begins by conducting a SWOT analysis to see the company's position in the SWOT quadrant, then using the BSC method in a policy model that meets four measurement perspectives. Based on the results of the Process Hierarchy Analysis (AHP) method, it was found that the customer perspective was the first priority with a weight of 0.416 in strategy implementation, followed by the growth and learning perspective, then the internal business perspective and finally the financial perspective.